Dietary supplementation in sport and exercise : evidence, safety and ergogenic benefits - Hoffman, Jay, 1961- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2019)
Dietary Supplementation in Sport and Exercise removes the myths associated with many dietary supplements. It provides an evidence-based approach to the physiological mechanisms related to popular supplements and examines the ergogenic benefits in both competitive and recreational athletes. This text covers a variety of supplements, including vitamins and minerals, carbohydrates, protein and amino acids, beta-alanine, creatine and guanidinoacetic acid, caffeine and probiotics, as well as emerging ergogenic aids. Information on dosage, ceiling effects and washout periods is discussed, along with safety and legality for different sporting organizations. The book also offers an insight into the efficacy of certain dietary supplements in unique populations, like children and the elderly. Dietary Supplementation in Sport and Exercise is an important resource for advanced undergraduate and graduate students on exercise science, health and nutrition courses, as well as strength coaches, athletic trainers, nutritionists and personal trainers, and medical professionals who consult with patients on dietary supplementation.
OCLC-licensed vendor bibliographic record.
Keywords: Dietary supplements; Athletes -- Nutrition; Exercise -- Nutritional aspects; HEALTH & FITNESS / Healthy Living; HEALTH & FITNESS / Holism; HEALTH & FITNESS / Reference; MEDICAL / Preventive Medicine; HEALTH & FITNESS / Exercise; MEDICAL / Biochemistry